Lost in Contrasted Strands of Dislocated Identity: A Study of Two Diasporic Characters, Tha'mma and Ila in Amitav Ghoshs The Shadow Lines (Stamford Journal of English, 2013)
DOI: http://dx.doi.org/10.3329/sje.v4i0.13490 Stamford Journal of English Vol.4 2008 pp.62-76